2004
DOI: 10.1002/cbdv.200490127
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biologically Active Bibenzyls from Bauhinia saccocalyx Pierre

Abstract: Four new bibenzyls, bauhinols A-D (1-4), together with the two known bibenzyls 5 and 6, were isolated from the roots of Bauhinia saccocalyx, and their structures were elucidated by analyses of spectroscopic data. Bauhinol A (1) exhibits significant cytotoxicity towards NCI-H187 (small-cell lung cancer), BC (breast cancer), and KB (oral-cavity cancer) cell lines, with IC50 values of 2.7-4.5 microg/ml. Bauhinol B (2) is cytotoxic against NCI-H187 (IC50 = 1.1 microg/ml) and BC (IC50 = 9.7 microg/ml) cell lines, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Bibenzyl compounds are present in the EtAc extract of Cremastra appendiculata (D. Don) Makino [19]. These compounds exerted significant cytotoxicity against small cell lung cancer NCI-H187 cells [20]. It has been reported that the EtAc extract exerted inhibitory effect on LA795 cell line (mouse lung adenocarcinoma cell line, as confirmed using MTT assay).…”
Section: Discussionmentioning
confidence: 88%
“…Bibenzyl compounds are present in the EtAc extract of Cremastra appendiculata (D. Don) Makino [19]. These compounds exerted significant cytotoxicity against small cell lung cancer NCI-H187 cells [20]. It has been reported that the EtAc extract exerted inhibitory effect on LA795 cell line (mouse lung adenocarcinoma cell line, as confirmed using MTT assay).…”
Section: Discussionmentioning
confidence: 88%
“…MeO groups at δ (C) 55.95 (MeO–C(3,5)), 8.19 (Me–C(4)). The presence of the two CH 2 C‐atoms together with twelve C‐atoms in the range of δ (C) 104.21 – 158.48 were used to characterize 1 as a bibenzyl . Comparison of the 1 H‐ and 13 C‐NMR data of 1 with those reported for bauhinol E, a compound isolated from Bauhinia purpurea , showed high similarity, except for the presence of the signal at δ (H) 3.75 ( s , 6 H) observed in the 1 H‐NMR spectrum of 1 , correlated in the HSQC with the signal at δ (C) 55.95 ( Table ), which was assigned to an additional MeO group (MeO–C(3,5)).…”
Section: Resultsmentioning
confidence: 95%
“…Since bibenzyls are reported to have cytotoxic activities, the new bibenzyl ( 1 ) has been evaluated against HL‐60 (human pro‐myelocytic leukemia), MCF‐7 (human breast adenocarcinoma), NCI‐H292 (human lung carcinoma) and HEP‐2 (human cervical adenocarcinoma) cell lines, using the MTT assay . Doxorubicin was used as the positive control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds were found to have potential uses in pharmaceuticals [4][5][6] and also in polymers. The number of biological properties of these compounds is containing anti-inflammatory, [7][8][9] antiproliferative, [10] antitumor [1] and anticancer, [10] antiplasmodial, [11] antihelminthic activity, [12] antibiotic activity, [13][14][15][16] antiestrogenic, [17] analgesic, [18] antipsychotic, [9,[19][20][21] angiotensin II receptor antagonistic, [22] antioxidant, [23] antimycobacterial, [24] and antiapoptosis. [25] Some of oxepine, benzoxepine, and dibenzoxepine derivatives have been synthesized by Tishchenko-like reaction, [26] Friedel-Crafts acylation reactions, [27] Suzuki coupling, [28] and Catellani reaction.…”
Section: Introductionmentioning
confidence: 99%